2002
DOI: 10.1111/1467-8624.00414
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Neurobehavioral Functioning, and Behavior Problems in School‐Age Children

Abstract: The aim of this study was to examine the associations between sleep and neurobehavioral functioning (NBF) in school-age children. These variables were assessed for 135 unreferred, healthy school children (69 boys and 66 girls), from second-, fourth-, and sixth-grade classes. Objective assessment methods were used on the participants in their regular home settings. Sleep was monitored using actigraphy for 5 consecutive nights; and NBF was assessed using a computerized neurobehavioral evaluation system, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
438
3
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(477 citation statements)
references
References 104 publications
28
438
3
8
Order By: Relevance
“…Other sleep issues such as sleeping less than others have also been associated with behavioural difficulties (Goodnight et al 2007;Gregory et al 2008a). Studies using actigraphy parental ratings of behaviour problems have also reported significant correlations between short sleep time or poor sleep quality and behavioural difficulties in school--age children (Aronen et al 2000;Sadeh et al 2002), although a similar study in adolescents failed to find such relationships (Moore et al 2009), possibly highlighting the importance of age when considering these phenotypic associations. As previously mentioned, twin studies have demonstrated possible overlap in the shared environmental influences affecting both sleep and behavioural difficulties.…”
Section: Sleep and Behavioural Difficulties: Associations Between Slementioning
confidence: 99%
“…Other sleep issues such as sleeping less than others have also been associated with behavioural difficulties (Goodnight et al 2007;Gregory et al 2008a). Studies using actigraphy parental ratings of behaviour problems have also reported significant correlations between short sleep time or poor sleep quality and behavioural difficulties in school--age children (Aronen et al 2000;Sadeh et al 2002), although a similar study in adolescents failed to find such relationships (Moore et al 2009), possibly highlighting the importance of age when considering these phenotypic associations. As previously mentioned, twin studies have demonstrated possible overlap in the shared environmental influences affecting both sleep and behavioural difficulties.…”
Section: Sleep and Behavioural Difficulties: Associations Between Slementioning
confidence: 99%
“…Nixon et al [20] reported that short sleep duration (\10 pt; 9.0 h) in 7-year-old children was related to emotional instability. Sadeh et al [25] associated sleep fragmentation with behavioral problems, but they did not report any findings related to sleep duration. To our knowledge, no previous studies have studied the association of short sleep and psychiatric symptoms among children \6 years old.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, children may be more prone to the effects of sleep deprivation than adults. For example, the association between neurocognitive functioning and sleep quality has been reported to be the strongest among the youngest children [25].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that rising early for school, even for as few as two days a week, results in greater complaints about difficulties in attention and concentration in the classroom by fifth grade children (Epstein, Chillag, & Lavie, 1998; see also . There is also some evidence that behavioral problems are more common in poor sleepers than in control age mates (Sadeh, Gruber, & Raviv, 2002).…”
Section: Introductionmentioning
confidence: 99%